ANALYSIS OF MATHS LEARNING ANXIETY IN STUDENTS OF MADRASAH IBTIDAIYAH NEGERI (MIN) NORTH ACEH - Asmaul Husna; Novianti Novianti (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2025)
Learners' anxiety towards mathematics is influenced by the mathematics learning experiences they have received in the past. This study aims to describe the factors of maths anxiety, and how to overcome them based on students' learning outcomes. The subjects of this study were fifth grade students of MIN Aceh Utara based on groups with low, medium, and high learning outcomes. The subject retrieval technique used in this research is purposive sampling and snowball sampling with qualitative research methods with descriptive approaches and data collection techniques with observation, questionnaires, interviews, and documentation and data analysis techniques using Miles Huberman techniques. The results showed that the factors that cause mathematics learning anxiety are internal and external factors in students with low learning outcome categories, namely lack of confidence when working on mathematics problems, not understanding mathematical concepts so that they are anxious during exams, and fear of facing mathematics subjects during offline learning and students with moderate learning outcome categories, namely lack of confidence when working on mathematics problems, lack of understanding of mathematical concepts so that they are anxious during exams, and fear of not being able to solve mathematical problems in front of the class while students with high learning outcome categories are anxious if they don't get good grades, feel uncomfortable if there is a student with a high learning outcome category.Keywords: Maths Learning Anxiety; Factors; Ways to Overcome; MIN students